Peroral endoscopic myotomy (POEM) vs pneumatic dilation (PD) in treatment of achalasia: A meta-analysis of studies with ≥ 12-month follow-up - Ofosu, Andrew; Mohan, Babu P.; Ichkhanian, Yervant; Masadeh, Maen; Febin, John; Barakat, Mohamed; Ramai, Daryl; Chandan, Saurabh; Haiyeva, Gulara; Khan, Shahab R.; Aghaie Meybodi, Mohamad; Facciorusso, Antonio; Repici, Alessandro; Wani, Sachin; Thosani, Nirav; Khashab, Mouen A. (Endoscopy International Open, 2021)
Background and study aims Peroral endoscopic myotomy (POEM) is increasingly being used as the preferred treatment option for achalasia. The aim of this systematic review and meta-analysis was to compare the efficacy and safety of POEM versus pneumatic balloon dilation (PD).Methods We performed a comprehensive review of studies that reported clinical outcomes of POEM and PD for the treatment of achalasia. Measured outcomes included clinical success (improvement of symptoms based on a validated scale including an Eckardt score ≤ 3), adverse events, and post-treatment gastroesophageal reflux disease (GERD).Results Sixty-six studies (6268 patients) were included in the final analysis, of which 29 studies (2919 patients) reported on POEM and 33 studies (3050 patients) reported on PD and 4 studies (299 patients) compared POEM versus PD. Clinical success with POEM was superior to PD at 12, 24, and 36 months (92.9 %, vs 76.9 % P = 0.001; 90.6 % vs 74.8 %, P = 0.004; 88.4 % vs 72.2 %, P = 0.006, respectively). POEM was superior to PD in type I, II and III achalasia (92.7 % vs 61 %, P = 0.01; 92.3 % vs 80.3 %, P = 0.01; 92.3 %v 41.9 %, P = 0.01 respectively)Pooled OR of clinical success at 12 and 24 months were significantly higher with POEM (8.97; P = 0.001 & 5.64; P = 0.006). Pooled OR of GERD was significantly higher with POEM (by symptoms: 2.95, P = 0.02 and by endoscopic findings: 6.98, P = 0.001). Rates of esophageal perforation (0.3 % vs 0.6 %, P = 0.8) and significant bleeding (0.4 % vs 0.7 %, P = 0.56) were comparable between POEM and PD groups.Conclusions POEM is more efficacious than PD in the treatment of patients with achalasia during short-term and long-term follow-up, albeit with higher risk of abnormal esophageal acid exposure.